"Movement stabilization of the parrot mambo quadcopter along a given trajectory based on PID controllers". Issue 13 (2021) - Trenev, I.; Tkachenko, A.; Kustov, A.
Abstract: In this work, the mathematical model of quadcopter is given in both nonlinear and linearized forms and open-loop control is constructed based on the set point for a linear model of a quadcopter, as well as coefficients of PID controllers is carried out. A numerical simulation has been performed in the Matlab/Simulink environment. This work considers a fairly stable and easy-to-implement control law for a quadrocopter, which can be applied in various social spheres.